Revealed comparative advantage in the internal market - Mika Widgrén (The Research Institute of the Finnish Economy (ETLA), 2005)
This paper investigates comparative advantage and its development across selected Asian, American and European countries between 1996 and 2002. In doing so, we calculate the Balassa index of revealed comparative advantage using industry data at the HS 4-digit level. The major part of the analysis concentrates on the factor intensities of the sample countries' comparative advantage and the overlap between them in the Internal Market. The paper shows that there is clearly some convergence in terms of the factor content of comparative advantage between Asian countries, the new member states and the EU15. The EU's comparative advantage has recently moved towards intensive use of both human and physical capital.
Keywords: 330; Comparative advantage; factor intensity; globalisation; Komparativer Kostenvorteil; Faktorintensität; Vergleich; EU-Staaten; Asien; Russland; Amerika; Balassa-Samuelson Effekt